2002
DOI: 10.1099/0022-1317-83-6-1291
|View full text |Cite
|
Sign up to set email alerts
|

Genomic characterization of TT viruses (TTVs) in pigs, cats and dogs and their relatedness with species-specific TTVs in primates and tupaias

Abstract: Using PCR with primers derived from a non-coding region of the human TT virus (TTV) genome, the TTV sequence in serum samples obtained from pigs (Sus domesticus), dogs (Canis familiaris) and cats (Felis catus) was identified and the entire genomic sequence was determined for each representative isolate. Three TTV isolates (Sd-TTV31 from a pig, Cf-TTV10 from a dog and Fc-TTV4 from a cat) comprising 2878, 2797 and 2064 nucleotides, respectively, each had three open reading frames (ORFs) encoding 436-635 (ORF1), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
134
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(139 citation statements)
references
References 41 publications
(66 reference statements)
4
134
1
Order By: Relevance
“…TTSuVs have similar genomic organization with human-infecting TTVs but share less than 45 % nt sequence identity (Niel et al, 2005;Okamoto et al, 2002). Recent studies also demonstrated a high degree of genetic variability between TTSuV1 and TTSuV2 (Cortey et al, 2011).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…TTSuVs have similar genomic organization with human-infecting TTVs but share less than 45 % nt sequence identity (Niel et al, 2005;Okamoto et al, 2002). Recent studies also demonstrated a high degree of genetic variability between TTSuV1 and TTSuV2 (Cortey et al, 2011).…”
Section: Introductionmentioning
confidence: 96%
“…Discrepancies observed between studies suggest that the genomic diversity found in TTV isolates can be associated with different strategies of expression and localization of viral proteins (Müller et al, 2008). It has been suggested that the transcriptional profile of TTSuV would be similar to that found in human TTVs (Okamoto et al, 2002), but experimental evidence is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Even though TTV could infect several species, including human, horse, dog, cat, and pig, TTV has shown host specificity and variable genomic length within the order of the animal. 17,20 The genomic length of TTV in humans and primates is approximately 3.8 kb in length and is approximately 2.9 kb in pigs and dogs. Swine TTV has also shown worldwide distribution, and a high seropositive ratio in the general pig population has been reported.…”
mentioning
confidence: 99%
“…This virus was first isolated from a Japanese man with non A-E post-transfusional hepatitis (Nishizawa et al 1997). Since then, TTV has been shown to infect humans, non-human primates, and farm animals (Leary et al 1999, Okamoto et al 2000, 2001, 2002, Brassard et al 2008.…”
Section: Introductionmentioning
confidence: 99%
“…The first full genome analysis of TTSuV was completed by Okamoto et al (2002), and the differentiation of TTSuV into separate species was performed by Niel et al (2005). TTSuV belongs to the family Anelloviridae and is classified into the species TTSuV1a (represented by Sd-TTV31 strain) and TTSuV1b (represented by Sd-TTV1p strain) in the genus Iotatorquevirus, and TTSuVk2 (represented by Sd-TTV2p strain) in the genus Kappatorquevirus (ICTV 2012).…”
Section: Introductionmentioning
confidence: 99%